Southeast Missouri from swampland to farmland the transformation of the lowlands - Fisher, John C. 1949- (McFarland & Company, Inc., Publishers, 2017)
Geology and geography of the lowlands -- The first inhabitants -- Euro-American settlement to 1811 -- The New Madrid earthquakes -- Settlement, early agriculture and civil war -- Transportation -- Timber -- Beginning reclamation -- Little River Drainage District : organization and opposition -- Little River Drainage District : planning and construction -- Little River Drainage District : floods, the Great Depression, financial failure and recovery -- Land promotion, post-drainage agriculture and social change -- New political and religious movements and the sharecropper demonstration -- Politics and farm labor changes -- End of an era
Includes bibliographical references (pages 231-237) and index
Keywords: Geschichte 1800-1950; Landwirtschaft; Urbarmachung; Staat Missouri -- Südost; Cape Girardeau, Mo.